A Clinicopathological Study on Cases of Hodgkin’s Diseases in IraqiChildren Attending AL-Kadhimiyia Teaching Hospital - Abbas, Sawsan S. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Hodgkin’s Diseases is a group of cancers characterized by Reed- Sternberg cells, aneuoploid cells that usually express CD15 and CD30. Several epidemiological and serological studies support the role of Epstein –Barr virus in the pathogenesis of Hodgkin’s Diseases Patients and Method: A retrospective study was done where by twenty cases were collected from the Pediatric Oncology Clinic in AL-Kadhyimia Teaching Hospital over a period of five years from the first of January 2002 – end of December 2006.Information was taken from the patient’s records in the Pediatric Oncology Clinic including age at presentation, sex, physical finding, histopathological subtypes, staging , treatment applied , outcome and follow up Results: Among the studied group 14 cases ( 70%) were males and 6 cases (30%) were females , male : female ratio equal to 2.3:1, rang of age was between 5- 16 years with a peak age at presentation was between 11- 15 years. The initial presentation was an enlarged cervical lymph node in 18 cases ( 90%), histopathologically , most of the patients had mixed cellularity subtype , 9 cases (45%), stage II and stage III comprise the majority of cases 8 cases for each (40%), B symptoms were reported in 13 cases ( 65%) . Chemotherapy was the mainstay of treatment with good response. The overall survival was (90%), 18 cases over a median period of follow up of 2-5 years. One case relapses two months after the end of treatment, no death. Conclusion: Although mixed cellularity was encountered in most of our patients but the response to chemotherapy is good.